PPAR-γ, Microglial Cells, and Ocular Inflammation: New Venues for Potential Therapeutic Approaches. (11th March 2008) - Malchiodi-Albedi, Fiorella; Matteucci, Andrea; Bernardo, Antonietta; Minghetti, Luisa
Abstract : The last decade has witnessed an increasing interest for the role played by the peroxisome proliferator-activated receptor-γ (PPAR-γ ) in controlling inflammation in peripheral organs as well as in the brain. Activation of PPAR-γ has been shown to control the response of microglial cells, the main macrophage population found in brain parenchyma, and limit the inflammation. The anti-inflammatory capacity of PPAR-γ agonists has led to the hypothesis that PPAR-γ might be targeted to modulate degenerative brain diseases in which inflammation has been increasingly recognized as a significant component. Recent experimental evidence suggests that PPAR-γ agonists could be exploited to treat ocular diseases such as diabetic retinopathy, age-related macular degeneration, autoimmune uveitis, and optic neuritis where inflammation has relevant role. Additional PPAR-γ agonist beneficial effects could involve amelioration of retinal microcirculation and inhibition of neovascularization. However, PPAR-γ activation could, in some instances, aggravate the ocular pathology, for example, by increasing the synthesis of vascular endothelial growth factor, a proangiogenic factor that could trigger a vicious circle and further deteriorate retinal perfusion. The development of new in vivo and in vitro models to study ocular inflammation and how to modulate for the eye benefit will be instrumental for the search of effective therapies.